Safeguarding Educators: The Role of Restorative Justice in Teacher Professional Protection - Labaka, Albri; Raharjo, Trisno (CV. Strata Persada Academia, 2025)
This study uses a normative juridical approach that focuses on Law Number 14 of 2005 concerning Teachers and Lecturers to look at legal protection for teachers from potential criminalization. The results show a disharmony in regulations, especially between Law No. 23 of 2002 concerning Child Protection and Law No. 14 of 2005 concerning Teachers and Lecturers. This often creates legal uncertainty and allows for criminalizing pedagogical actions that should be protected. Because the restorative justice approach considers the purpose of the action, the social impact, and the relationship between the perpetrator, the victim, and the educational environment, it is considered more appropriate and equitable in these situations. According to the analysis, some of the policy recommendations are as follows: changes in regulations governing the roles and responsibilities of teachers; the application of the principle of restorative justice in the legal education curriculum; the establishment of educational mediation institutions at the local level; implementation of legal campaigns based on empathy and education; legal preventive protection for educators; and regular evaluation of its implementation.